A Comparative Study on Student Engagement and Achievement in Online Versus Traditional Classroom Instruction - Ashokkumar, N.; Venkatramana, P.; Arun, V.; Prabhu, S. (Journal of Engineering Education Transformations, 2025)
The different points related to the study topic and Vygotsky’s theory have been stated. The transition of traditional learning to digital learning has faced great changes mainly in this time of pandemic. The primary data collection process, descriptive method, and deductive approach of research have followed here. SPSS and ANOVA, frequency analysis, and correlation have been done here. Data has been gathered from different 55 students with 13 questions and their analysis is been stated here. The interpretation of data has been done with SPSS in this part. A comparison of the literature review and the relation between the results that are collected are analysed in this part. Thus, it can be concluded that the traditional learning practice created more impact on the engagement of students. The online teaching process has made less engagement in comparison with the traditional process. Students who wished to attend international classes but could not go to the places are taking online classes from home. Nevertheless, the relationship between the teacher and the student and their successes are hindered here so much so.